2011
DOI: 10.1002/rcm.4873
|View full text |Cite
|
Sign up to set email alerts
|

Suppression correction and characteristic study in liquid chromatography/Fourier transform mass spectrometry measurements

Abstract: Analysis of peptide profiles from liquid chromatography/Fourier transform mass spectrometry (LC/FTMS) reveals a nonlinear distortion in intensity. Investigation of the measured C13/C12 ratios comparing with theoretical ones shows that the nonlinearity can be attributed to signal suppression of low abundance peptide peaks. We find that the suppression is homogenous for different isotopes of identical peptides but non-homogenous for different peptides. We develop an iterative correction algorithm that corrects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…We can see that including more isotopes introduces larger bias in measured H/L ratios. This agrees very well with our previous research on instrument suppression [5]. On the other hand, using two or three isotopes provides the least variance, which agrees with our analysis on variance reduction.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We can see that including more isotopes introduces larger bias in measured H/L ratios. This agrees very well with our previous research on instrument suppression [5]. On the other hand, using two or three isotopes provides the least variance, which agrees with our analysis on variance reduction.…”
Section: Resultssupporting
confidence: 92%
“…In this sense, the more isotopes we consider, the lower the variance on abundance estimation. However, in [5], it is revealed that most peptide intensities are suppressed to a degree. Thus, to reduce the distortion on ratio measurement, it is better to use fewer isotopes.…”
Section: ) Noise Model and Instrument Suppression Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as illustrated in Figure 3, our past research shows severe distortion of normalized 12 C/ 13 C ratios in a LC-MS measurement [1]. Without distortion, the normalized ratios as listed in (1) should be centered at one, but in Figure 3 the ratios are mostly under one.…”
Section: Improved Methodsmentioning
confidence: 94%
“…Without distortion, the normalized ratios as listed in (1) should be centered at one, but in Figure 3 the ratios are mostly under one. 12 13 .…”
Section: Improved Methodsmentioning
confidence: 98%